Microstructural Investigation and Wear Characteristics of Al-Si-Ti Cast Alloys - SUBHI, Akeel Dhahir; KHLEIF, Ali Abbar; ABDUL-WAHID, Qasim Saad (Engineering Transactions, 2020)
Hypoeutectic Al-7Si alloys containing various titanium proportions (0.8–1.6%) were produced and analyzed in this work. The wear characteristics of Al-Si alloys were studied under the conditions of dry sliding at various applied loads. Optical microscope (OM), scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to depict the microstructure, worn surface and phases, respectively. Phases of α-Al, eutectic and Ti9Al23 were recognized in the Al-Si-Ti alloys matrix. Considerable coarsening took place in α-Al and eutectic silicon in a fully eutectic through solidification. The hardness was increased as the titanium proportion increased. Furthermore, significant changes were found in the wear rate depending on the titanium proportion added and load applied.